1974
DOI: 10.1037/h0035829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of worker orientation differences on job attitude correlates.

Abstract: Correlations between various worker attitudes and job motivation, performance, and absenteeism were examined for 290 skilled and semiskilled papermakers. The hypothesis that significant relationships occur more frequently for those employees least job involved was supported, inasmuch as they accounted for 84% of the significant correlations. Further analyses disclosed twice as many associations for skilled as for semiskilled employees. Thus, highly involved employees, more intrinsically oriented toward their j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Because job involvement can affect the degree of an employee's effort and motivation (Holmes & Srivastava, 2002) and some important OCB antecedents (e.g., job satisfaction), it follows that job involvement may affect OCB (Diefendorff et al). Moreover, Wood (1974) pointed out that employees with high job involvement are more independent and self-confident-they not only conduct their work in accordance with the job duties required by the company but are also more likely to do their work in accordance with the employees' perception of their own performance. Wood went a step further and suggested that job involvement originates in intrinsic satisfaction and thus should be related to job performance that provides intrinsic rewards (i.e., helping behavior or OCB).…”
Section: Job Involvement As a Mediator Of The Job Characteristics-ocbmentioning
confidence: 99%
“…Because job involvement can affect the degree of an employee's effort and motivation (Holmes & Srivastava, 2002) and some important OCB antecedents (e.g., job satisfaction), it follows that job involvement may affect OCB (Diefendorff et al). Moreover, Wood (1974) pointed out that employees with high job involvement are more independent and self-confident-they not only conduct their work in accordance with the job duties required by the company but are also more likely to do their work in accordance with the employees' perception of their own performance. Wood went a step further and suggested that job involvement originates in intrinsic satisfaction and thus should be related to job performance that provides intrinsic rewards (i.e., helping behavior or OCB).…”
Section: Job Involvement As a Mediator Of The Job Characteristics-ocbmentioning
confidence: 99%
“…This clearly indicates the role of work and job design in enhancing job involvement. It is also clear that employees with high job involvement are more self-determining and self-assured (Wood, 1974). Job involvement can be linked to decision-making and decision to produce (March & Simon, 1958).…”
Section: Job Involvementmentioning
confidence: 99%
“…Reviewing several studies related to job involvement and organizational commitment revealed correlations of (r = 0.50) between job involvement and job satisfaction, job satisfaction and organizational commitment and correlation between organizational commitment and job involvement (Cheloha & Farr, 1980;Gechman & Wiener, 1975;Hall & Schneider, 1972;Mowday, Porter & Steers,1982;Mowday, Steers, & Porter, 1979;Rabinowitz & Hall, 1977;Weissenberg & Gruenfeld, 1968;Wood, 1974).…”
Section: Job Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Also included were measures --reflecting confidence and trust between supervisors and subordinates (Flacks, 1969;Sells, 1968a;Wood , 1974).…”
Section: Ind Ividual Level Measuresmentioning
confidence: 99%